Waldenström's macroglobulinemia associated with cryoglobulinemia: Pathogenetic, clinical, and therapeutic aspects - Dimopoulos, M.A.; Kastritis, E. (HCV Infection and Cryoglobulinemia, 2012)
Waldenström's macroglobulinemia (WM) is a distinct B-cell lymphoproliferative disorder that is characterized by infiltration of the bone marrow with lymphoplasmacytic cells and by an IgM monoclonal gammopathy. Both type I and type II cryoglobulins may be associated with WM. About 10-20% of patients with the diagnosis of WM have cryoglobulins, but clinically evident type I cryoglobulinemia occurs in less than 5% of WM patients. In type I cryoglobulinemia, the signs and symptoms are mainly related to the physicochemical properties of the monoclonal IgM and immune phenomena do not develop. In type II cryoglobulinemia, the symptoms are related to the immune phenomena, with vasculitis of small and medium-sized vessels as the most common finding. However, the clinical features of types I and II cryoglobulinemia may overlap. Plasmapheresis/plasma exchange is very effective for the immediate reduction of the amount of circulating type I cryoglobulins and immediate anti-lymphoma treatment with highly effective regimens should be considered concomitantly or following plasma exchange. In WM patients with type II cryoglobulinemia, plasmapheresis may not be as effective and immunosuppressive therapies should be considered, including rituximab. © 2012 Springer-Verlag Italia. All rights reserved.